2014
DOI: 10.7162/s1809-97772013000100010
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implants and bacterial meningitis: A speech recognition study in paired samples

Abstract: Summary Introduction: Cochlear implants may guarantee sound perception and the ability to detect speech at a close-to-normal hearing intensity; however, differences have been observed among implantees in terms of performance on discrimination tests and speech recognition. Objective: To identify whether patients with post-meningitis deafness perform similarly to patients with hearing loss due to other causes. Method: A retrospective clinical study involving post-lingual patients who had been using Nucleus-22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Consistent with El-Kashlan et al, a recent study done by Ikeya et al [10] on adults demonstrated that patients with post-meningitic deafness benefitted significantly from cochlear implantation; however, the audiological outcomes were still hard to predict in some cases, especially in the presence of ossification [10]. In the one year follow-up after utilizing the device, assessment of speech recognition revealed poorer results in cochlear implant recipients with hearing loss due to bacterial meningitis than those with hearing loss due to other causes who used the device for the same period of time [17]. In an Iranian study, a survey was done for the assessment of CI outcomes in the form of auditory and speech abilities in post-meningitis deaf children and revealed that outcomes were not the same as in non-meningitis deaf children.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with El-Kashlan et al, a recent study done by Ikeya et al [10] on adults demonstrated that patients with post-meningitic deafness benefitted significantly from cochlear implantation; however, the audiological outcomes were still hard to predict in some cases, especially in the presence of ossification [10]. In the one year follow-up after utilizing the device, assessment of speech recognition revealed poorer results in cochlear implant recipients with hearing loss due to bacterial meningitis than those with hearing loss due to other causes who used the device for the same period of time [17]. In an Iranian study, a survey was done for the assessment of CI outcomes in the form of auditory and speech abilities in post-meningitis deaf children and revealed that outcomes were not the same as in non-meningitis deaf children.…”
Section: Discussionmentioning
confidence: 99%
“…The SIR results in children with prelingual deafness were comparable in stages I and II, but higher in the case of postlingual deafness -hence the age at which the child suffers BM is significant [30]. While cochlear implants play an important role in restoring sound perception and speech detection, work by de Brito [61] showed that those children whose hearing loss was due to BM did not achieve, a year after receiving an implant, such good results in speech recognition tests (open and closed sets) as children who had received implants for other reasons. According to Liu [62], labyrinthitis ossificans can adversely affect speech perception after implantation, but other preimplantation (and pre-BM) factors can also play a part, including neurological deficits, age at deafness, and length of deafness -further research is needed.…”
Section: Early Cochlear Implantantion In Children After Bmmentioning
confidence: 98%
“…A betegek hanghallásról már közvetlenül az első állítást követően beszámoltak, beszéd értésük azonban minden esetben jóval elmaradt a várttól, beszédteszteket emiatt végezni nem tudtunk egyik betegünknél sem. Megfigyeléseink összhangban vannak az irodalmi adatokkal, hiszen a meningitisen átesett betegeknél több vizsgálat is kimutatta, hogy a beszédértés elmarad a más etiológiájú halláscsökkenés miatt implantáción átesett betegek halláseredményeitől [19][20][21]. Betegeinknél a jó hallásküszöb mellett megfigyelhető rossz beszédértéshez feltehetőleg hozzájárulnak a meningitis kapcsán kialakult centrális idegrendszeri károsodások, melyek a hallópályákat és a cortexet érintik [6].…”
Section: Megbeszélésunclassified